Clinical event rate in patients with and without left main disease undergoing isolated coronary artery bypass grafting: results from the European DuraGraft Registry. (5th August 2022) - Caliskan, Etem; Misfeld, Martin; Sandner, Sigrid; Böning, Andreas; Aramendi, Jose; Salzberg, Sacha P; Choi, Yeong-Hoon; Perrault, Louis P; Tekin, Ilker; Cuerpo, Gregorio P; Lopez-Menendez, Jose; Weltert, Luca P; et al.
Abstract: OBJECTIVES: Left main coronary artery disease (LMCAD) is considered an independent risk factor for clinical events after coronary artery bypass grafting (CABG). We have conducted a subgroup analysis of the multicentre European DuraGraft Registry to investigate clinical event rates at 1 year in patients with and without LMCAD undergoing isolated CABG in contemporary practice. METHODS: Patients undergoing isolated CABG were selected. The primary end point was the incidence of a major adverse cardiac event (MACE) defined as the composite of death, myocardial infarction (MI) or repeat revascularization (RR) at 1 year. The secondary end point was major adverse cardiac and cerebrovascular events (MACCE) defined as MACE plus stroke. Propensity score matching was performed to balance for differences in baseline characteristics. RESULTS: LMCAD was present in 1033 (41.2%) and absent in 1477 (58.8%) patients. At 1 year, the MACE rate was higher for LMCAD patients (8.2% vs 5.1%, P  = 0.002) driven by higher rates of death (5.4% vs 3.4%, P  = 0.016), MI (3.0% vs 1.3%, P  = 0.002) and numerically higher rates of RR (2.8% vs 1.8%, P  = 0.13). The incidence of MACCE was 8.8% vs 6.6%, P  = 0.043, with a stroke rate of 1.0% and 2.4%, P  = 0.011, for the LMCAD and non-LMCAD groups, respectively. After propensity score matching, the MACE rate was 8.0% vs 5.2%, P  = 0.015. The incidence of death was 5.1% vs 3.7%, P  = 0.10, MI 3.0% vs 1.4%, P  = 0.020, and RR was 2.7% vs 1.6%, P  = 0.090, for the LMCAD and non-LMCAD groups, respectively. Less strokes occurred in LMCAD patients (1.0% vs 2.4%, P  = 0.017). The MACCE rate was not different, 8.5% vs 6.7%, P  = 0.12. CONCLUSIONS: In this large registry, LMCAD was demonstrated to be an independent risk factor for MACE after isolated CABG. Conversely, the risk of stroke was lower in LMCAD patients. Clinical trial registration number: ClinicalTrials.gov NCT02922088. Abstract : Due to the large myocardial territory at risk, high ischaemic burden and the overall higher atherosclerotic burden in the aorta or other peripheral arteries, coronary artery disease (CAD) with the involvement of the left main (LM) coronary artery is commonly considered to be associated with significant morbidity and mortality [1–3].